A quantitative real-time PCR method for in planta monitoring of Phytophthora infestans growth - Llorente, Briardo (2010)
Aims: To establish a reliable and rapid protocol to simultaneously obtain high quality DNA from an infected host plant and the infecting pathogen. To develop an accurate and sensitive low-cost assay for the quantification and in planta monitoring of Phytophthora infestans growth.Methods and Results: In this study, we describe a SYBR Green-based quantitative real-time PCR (qPCR) method for the quantification of P. infestans. The method is based on a simultaneous plant-pathogen DNA purification followed by a qPCR in which the relative quantification of pathogen and plant DNA is performed. Besides assuring an accurate quantification, the use of a plant gene provides a reliable indicator of sample quality, allowing the exclusion of inappropriate samples. By applying this methodology, we were able to detect P. infestans in potato leaf and tuber tissue before the first symptoms of the disease were observed and to monitor the in planta growth of the pathogen for 6 days.Conclusions: This is a reliable low-cost assay that provides rapid, accurate and sensitive quantification of the late blight pathogen, allowing the in planta monitoring of P. infestans growth.Significance and Impact of the Study: The quantitative nature of the assay described in this study may be useful in plant breeding programmes and basic research. The method is appropriate for the comparison of cultivars with different, and even subtle, degrees of pathogen resistance and in the screening of new anti-oomycete compounds. The method can be easily adapted to tomato and the model plant Nicotiana benthamiana.